Identifikasi Risiko yang Mempengaruhi Pelaksanaan Proyek Konstruksi Jalan di Kota Palu Berdasarkan Persepsi Konsultan - Fahirah, F.; Tlantan, J.S. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2022)
In the implementation of a road construction project in any form and anywhere will never avoid risk, both small risk and big risk. The larger the scale of a construction project, the greater the possibility of risks that will occur if these risks are not managed properly. The purpose of this study was to identify risks that affect the implementation of road construction projects based on the perceptions of the consultants. Primary data was collected through the distribution of questionnaires to consulting companies that have supervised the implementation of road construction. The data was processed using descriptive statistics, Relative Rank Index (RRI) and Correlation Analysis. The results showed that 5 dominant risks were identified that affected the implementation of road construction based on the consultant's perception, namely 1) Using inappropriate work methods would make work late (RRI = 0.896), 2) Wrong Planning Data of DED (Detail Engineering Design)  that resulted in frequent design review (RRI = 0.880), (3) inefficient use of heavy equipment makes work productivity not achieved according to plan (RRI = 0.864), (4) limited field workers resulting in productivity cannot be maximized (RRI = 0.864, (5) maintenance affects the level of damage to heavy equipment (RRI = 0.824). The risk of using an inappropriate work methods would make the work late is strongly correlated with the risk of limited field workers resulting in productivity cannot be maximized, with a correlation value of 0.542.